An investigation of the potential anti-inflammatory properties of novel compounds with respect to LFA-1 mediated T cell motility and cytotoxicity profiling - Coppins, Jennifer P. (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2009)
The aim of this thesis was to investigate the effects in vitro of novel compounds on LFA-1 mediated T cell motility, and, to develop a profile of the compounds with respect to cytotoxicity and apoptosis. The compounds evaluated in this work were categorised as those that are synthetic derivatives of the naturally occurring pharmacological products from the fern Pteridium aquilinum, which had previously been evaluated in animal models of inflammation, denoted with a prefix PH. Following a pilot study, the following were chosen for further investigation; 6C6, 6C6-OH,7C9 and 7C17 based on activity demonstrated and to examine the potential with varying structures. PH 6 (6C6) had demonstrated significant efficacy in animal models of inflammation. A second group of compounds were isolated in house, known as quinones, and are denoted with a prefix HIH. This group of compounds were also assessed for their inhibitory properties in LFA-I mediated T cell motility. The cytotoxicity of these compounds was restricted to investigation in MTT and LDH assays owing to limited quantities. This thesis opens with an introduction that describes inflammation and autoimmunity with the emphasis on T cell involvement. The process of, and molecules involved in LFA-I mediated T cell motility are also described. Cytotoxicity and apoptosis are introduced, and the involvement of apoptosis in the regulation of the immune system is also described.
Keywords: Pharmacy, Ph.D.; Ph.D. Trinity College Dublin